Challenges faced by state House of Assembly on Oversighting Public Sectors in Nigeria: study of Bauchi State House of Assembly Bauchi State - N. Adamu; M. Magaji; Y. I. Gadau; A. M. Malami (Australian Journal of Business and Social Science, 2026)
Globally nations strike to achieve good governance, and this effort requires institutional function and in a democratic set up, legislature serves as an institution that ensures smooth policies implementation, oversighting executives to ensure compliance with acts and laws of the country. Nigeria as a country is not exceptional and it legislature serve as instrument of good governance through representation, oversight and law making and yet they face the challenges that affect their oversighting function especially at state house of assemblies. This paper is set to examine the challenges affecting state house of assemblies on oversighting public sectors a study of Bauchi State House of Assembly. The paper employed face to face interview as a means of data collection and thematic analysis was used in discussing the findings. saturation principle was used in interviewing 8 informants. The findings reveal that lack of financial autonomy hinders legislature to oversight the ministries, departments and agencies because of lack of logistic support. Party affiliation is also a detriment to members of the ruling party side with executives. Similarly, lack of cooperation by the MDAs hinders legislative members in obtaining relevant information especially finance records. The paper recommended that legislature as an institution should be given full financial autonomy to discharge it duties effectively, secondly Executives branch should see legislators as friends of progress and work hand in hand with them to enable them to carry out their constitutional responsibility. Training and re -training should be given on legislative activities such as oversight to legislators to improve their expertise and skills that would yield positive outcomes.